Effect of platelet-rich plasma on temporomandibular joint cartilage wound healing: Experimental study in rabbits. Issue 2 (February 2019) - Coskun, Ummugulsum; Candirli, Celal; Kerimoglu, Gokcen; Taskesen, Fatih
Abstract: Purpose: The aim of the study is to evaluate the effect of platelet-rich plasma (PRP) injection on temporomandibular joint (TMJ) cartilage and subchondral bone healing. Materials and methods: Sixteen New Zealand rabbits were divided into two groups, including single PRP and multiple PRP injection groups. Sodium mono-iodoacetate (MIA) was injected bilaterally into the TMJ of all rabbits to create osteoarthritis (OA). PRP was injected once into the right TMJ in the single PRP group and was injected three times (once a week) into the right TMJ in the multiple injection group 4 weeks after injection of MIA. At the time of each PRP injection, isotonic NaCl solution was injected into the left TMJ in the control groups. All animals were sacrificed 30 days after the first PRP injection. Results: As a result of the histological evaluation, there was no statistically significant difference in cartilage and subchondral bone regeneration between the groups (p > 0.05). Conclusions: Although there was no statistically significant difference between PRP and control groups, it was seen that improvement were better in PRP groups. According to the Results of our study, it seems that different methods should be tried to investigate the efficacy of PRP on the TMJ healing.